Historic ranches of the Old West - O'Neal, Bill (Austin, Tex. : Eakin Press, 1997)
A number of ranch headquarters still serve their original function, others are museums or guest ranches. This book offers a visit back to a romantic and fascinating era.
Includes bibliographical references (p. 335-345) and index.
72295
Keywords: Ranches -- History. -- Southwest, New; Ranchers -- Biography. -- Southwest, New; Ranch life -- History. -- Southwest, New; Southwest, New -- History, Local